3-D numerical study of the effect of fin discontinuity on heat transfer augmentation in pipes having internal longitudinal fins for turbulent compressible flow - Saqr, Khalid M. (UTM, 2008)
Pipes with internal longitudinal fins are ideal to be utilized in flow-based waste heat recovery applications. They provide significantly higher heat transfer coefficient than plain pipes, and lower pressure drop than helically finned pipes. This paper investigates the effect of fin discontinuity on the convective heat transfer coefficient. A 3-D finite volume numerical solution of Reynolds- Averaged Navier-Stokes equations for steady, compressible and turbulent flow is presented. Stanton number, Nusselt number and the convective heat transfer coefficient are computed for five different geometries at constant heat transfer coefficient on the outer wall. The effects of both continuous and discontinuous fins on heat transfer are elucidated. A new correlation to predict the temperature drop per unit length as a function of discontinuity offset distance is obtained.